2018
DOI: 10.1016/j.clon.2018.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Real-world Outcomes and Factors Predicting Survival and Completion of Radium 223 in Metastatic Castrate-resistant Prostate Cancer

Abstract: Younger age, completion of five to six cycles of Ra-223, lower alkaline phosphatase and neutrophil-to-lymphocyte ratio are predictors of overall survival. This is the first study to report neutrophil-to-lymphocyte ratio as an independent predictor of overall survival in a Ra-223 cohort. Good performance status and higher baseline haemoglobin predict the completion of five to six cycles of Ra-223.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
43
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 14 publications
8
43
0
1
Order By: Relevance
“…Recent studies have shown that patients with 1-4 doses of Ra-223 are more likely to have shorter OS than those with 5-6 doses. [15][16][17][18][19] The cessation of Ra-223 was associated with poor PS, severe pain, and a higher PSA level at baseline and a lower hemoglobin level at baseline. Likewise, the present study demonstrated that patients with PSA values of >100 ng/mL at baseline and PS ≥2 were more likely to have worse PFS with Ra-223.…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies have shown that patients with 1-4 doses of Ra-223 are more likely to have shorter OS than those with 5-6 doses. [15][16][17][18][19] The cessation of Ra-223 was associated with poor PS, severe pain, and a higher PSA level at baseline and a lower hemoglobin level at baseline. Likewise, the present study demonstrated that patients with PSA values of >100 ng/mL at baseline and PS ≥2 were more likely to have worse PFS with Ra-223.…”
Section: Discussionmentioning
confidence: 96%
“…As evidenced by several reports on the use of 223-Ra in the real world populations, accurate and careful selection of candidates for 223-Ra therapy has revealed to be as complex as strongly relevant 27 . Previous retrospective studies identified various prognostic variables associated with overall survival outcomes 28 , but the presence of validated therapy predictive factors is still lacking until now. In this context, there is a strong rationale to collect multicenter real-world data about patients treated with 223-Ra in clinical practice to assess the best modalities of application of this radiopharmaceutical agent and to test its tolerability and long-term outcomes in a selected range of mCRPC patients.…”
Section: Management Of Mcrpcmentioning
confidence: 99%
“…Besides documenting its effect on pain palliation, the pivotal phase 3 Alpharadin in Symptomatic Prostate Cancer Patients (ALSYMPCA) trial demonstrated the prognostic benefit that is induced by this radio-metabolic approach that prolonged overall survival (OS) and delayed time to the first symptomatic skeletal event with respect to the placebo arm [1]. However, in the last few years, some retrospective studies suggested that the OS benefit in real-life patients might be lower than that reported in the ALSYMPCA study [2][3][4][5]. These evidences might be explained either by the suboptimal sequence of Ra223 use in the castrate-resistant phase or as the result of a suboptimal selection of patients with poorer prognostic clinical characteristics.…”
Section: Introductionmentioning
confidence: 99%